Analysis of Sustainability of Culinary MSMEs through Increasing Competitiveness as an Intervening Variable - Gresela, Jenny; Supatminingsih, Tuti; Rahmatullah, Rahmatullah; Tahir, Thamrin; Inanna, Inanna (Universitas Negeri Semarang, 2024)
This study aims to identify the influence of education, business motivation, entrepreneurial literacy and digital literacy on the sustainability of culinary MSMEs in Makassar City which is mediated by increasing competitiveness. This study was conducted with a quantitative approach. Data collection techniques through observation and questionnaires while sample determination using purposive sampling which is adjusted to the analysis requirements used with a sample size of 180 respondents. The data analysis technique is Structural Equation Modeling (SEM) with Partial Least Square (PLS). This study found that the variables of education, business motivation, entrepreneurial literacy and digital literacy have an effect on the sustainability of culinary MSMEs in Makassar City which is mediated by increasing competitiveness. The results of this study serve as a reference that education and business motivation are very necessary in entrepreneurship and business actors also need to increase their knowledge of entrepreneurial literacy and digital literacy for the sustainability of MSMEs, especially in the culinary sector.